Associations between attachment and psychopathology dimensions in a large sample of patients with psychosis. Issue 1 (30th July 2015) - Korver-Nieberg, Nikie; Berry, Katherine; Meijer, Carin; de Haan, Lieuwe; Ponizovsky, Alexander M.
Abstract: Attachment theory is a powerful theoretical framework that complements and extents current models psychosis. We tested the hypothesis that attachment anxiety and avoidance are differentially associated with the severity of positive, negative and general psychopathology symptoms in patients with a diagnosis of psychosis. Five hundred patients with DSM-IV or ICD-10 diagnoses of psychotic disorders (schizophrenia, schizoaffective or non-affective psychosis) from independent samples from Netherlands, United Kingdom and Israel completed the Relationship Questionnaire. Psychopathology was assessed with the Positive and Negative Syndromes Scale. We used both categorical and dimensional approach to attachment data, which were analyzed using ANOVA with post-hoc tests, Pearson׳s correlations and multiple regression analysis. The conservative level of statistical significance was established ( p <0.001) to control for multiple testing. After adjustment for possible confounders, attachment anxiety predicted severity of positive symptoms as well as affective symptoms. Both attachment anxiety and avoidance were associated with severity of hallucinations and persecution Contrary to predictions, attachment avoidance was not associated with overall scores for negative symptoms, although there was some evidence of relatively weaker association between avoidance and social and emotional withdrawal. Highlights: The present study is the largest most comprehensive study assessing attachment and symptoms of psychosis to date. Attachment anxiety but not attachment avoidance is associated with the severity of positive and affective symptoms of psychosis. Our findings suggest that insecure attachment may be an important mechanism through which trauma exerts its effects on psychosis.